Opportunities, Enablers, and Barriers to the Use of Recorded Recovery Narratives in Clinical Settings - Roe, James; Brown, Susan; Yeo, Caroline; Rennick-Egglestone, Stefan; Repper, Julie; Ng, Fiona; Llewelyn-Beardsley, Joy; Hui, Ada; Cuijpers, Pim; Thornicroft, Graham; Manley, David; Pollock, Kristian; et al. (Frontiers in Psychiatry, 2020)
Background: Recorded Recovery Narratives (RRNs) describing first-person lived experience accounts of recovery from mental health problems are becoming more available. Little is known about how RRNs can be used in clinical practice and clinical education. Aims: The aim of this paper is to enable implementation planning for RRN interventions by identifying determinants of uptake. The objective was to identify opportunities, barriers and enablers to the uptake of RRN interventions in clinical practice and education. Method: Three phases of focus groups were conducted with multi-professional mental health clinicians. Phase 1 (4 groups, n=25) investigated current and possible uses of RRNs, Phase 2 (2 groups, n=15) investigated a specific intervention delivering recovery narratives. Phase 3 (2 groups, n=12) investigated clinical education uses. Thematic analysis was conducted. Results: RRNs can reinforce the effectiveness of existing clinical practices, by reducing communication barriers and normalising mental health problems. They can also extend clinical practice (increase hope and connection, help when stuck). Clinical considerations are the relationship with care pathways, choice of staff and stage of recovery. In educational use there were opportunities to access lived experience perspectives, train non-clinical staff and facilitate attitudinal change. Barriers and enablers related to design (ability to use online resources, accessibility of language, ability to individualise choice of narrative), risk (triggering content, staff skills to respond to negative effects), trust in online resource (evidence base, maintenance), and technology (cost of use, technology requirements). Conclusions: RRNs can both improve and extend existing clinical practice and be an important educational resource. RRNs can improve engagement and hope, and address internalised stigma. Beneficially incorporating RRNs into clinical practice and education may require new staff skills and improved technological resources in healthcare settings. Future work could focus on the use of peer support workers views on RRN use and how to avoid unnecessary and unhelpful distress.